Cinnamaldehyde Promotes the Intestinal Barrier Functions and Reshapes Gut Microbiome in Early Weaned Rats - Qi, Lili; Mao, Haiguang; Lu, Xiaohui; Shi, Tingting; Wang, Jinbo (Frontiers in Nutrition, 2021)
Cinnamaldehyde is an aromatic aldehyde isolated from the essential oil of cinnamon. It has been proved to possess various bioactivities such as anti-inflammation, anti-bacteria and antihypertensive. Nevertheless, early weaning could lead to intestinal stress, causing a range of intestinal health problems. The aim of this study is to explore the effects of cinnamaldehyde on gut barrier integrity, inflammatory responses, and intestinal microbiome of early weaned rats. In this study, treatment with cinnamaldehyde (100 or 200 mg/kg bodyweight/day) for 2 weeks significantly promoted the production of mucins in the colonic epithelial tissue of rats. Cinnamaldehyde supplementation significantly upregulated the expression of Muc2, TFF3 and the tight junction proteins (ZO-1, claudin-1, and occludin). Hematoxylin and eosin staining results showed that colonic histopathological changes were recovered by cinnamaldehyde supplementation. The mRNA expression of IL-6 and TNF-α were significantly decreased in the cinnamaldehyde groups while the TNF-α protein levels were significantly decreased in the two cinnamaldehyde groups. Cinnamaldehyde treatment obviously attenuated the activation of NF-κB signaling pathway in rat colonic tissue and suppressed the production of inflammatory cytokines. Furthermore, cinnamaldehyde supplementation remodeled the gut microbiome structure, at the genus level, Akkermansia,Bacteroides, Clostridium III, Psychrobacter, Intestinimonas were increased, whereas those of Ruminococcus, Escherichia/Shigellawere obviously decreased in the cinnamaldehyde treated groups. These findings indicated that cinnamaldehyde could effectively enhance intestinal barrier integrity, ameliorate inflammatory responses and remodel gut microbiome in early weaned rats.